1962
DOI: 10.1111/j.1365-246x.1962.tb02992.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Continents and Oceans on Geomagnetic Variations

Abstract: Summary During bays and similar magnetic variations the vectors representing changes in the geomagnetic field tend to lie on or close to a plane. The orientation of this plane varies from one observatory to another. At coastal observatories it almost invariably tilts upward towards the nearest deep ocean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(173 citation statements)
references
References 6 publications
3
169
0
1
Order By: Relevance
“…The efficiency of the reflection increases with increasing conductivity so that, for a perfect horizontal conductor, the vertical field component Z in induced by the internal currents cancels the external field variations Z ext . The attenuation of the vertical component and, in addition, an increase of the horizontal component are predicted for a horizontal uniform conducting lamina which is representative of the Earth surface (Parkinson, 1962). The same result is predicted by Price (1950) when a spatially uniform external field induces currents in a half-space of uniform conductivity.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…The efficiency of the reflection increases with increasing conductivity so that, for a perfect horizontal conductor, the vertical field component Z in induced by the internal currents cancels the external field variations Z ext . The attenuation of the vertical component and, in addition, an increase of the horizontal component are predicted for a horizontal uniform conducting lamina which is representative of the Earth surface (Parkinson, 1962). The same result is predicted by Price (1950) when a spatially uniform external field induces currents in a half-space of uniform conductivity.…”
Section: Introductionsupporting
confidence: 60%
“…For example, at a land-sea interface, lateral conductivity gradients cause large Z values, inland from the border of the sea, as for example at observatories on the coastline, since the higher seawater conductivity provides a larger vertical field with respect to the land. In this case, the variation field still lies in a plane, the "Parkinson plane", which is no longer horizontal but is tilted upward toward the sea (Parkinson and Jones, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The induction arrows provide an insight into the conductivity distribution in the subsurface around the Serra da Cangalha impact crater region. They showed that the real part of the Parkinson (1962) induction ar-rows for 0.1 and 1.0 s point towards the center of the crater. This behavior indicates the presence of a radial conducting structure at this level in the subsurface.…”
Section: Validity Of the 3d Model Resultsmentioning
confidence: 99%
“…Real tipper vectors in Parkinson 32 convention point towards the zone of high conductivity, whereas in Weise convention they point away from the zone of high conductivity. In the following we model tipper response recorded from the GHC.…”
Section: Three-dimensional Modelling Of Tipper Responsementioning
confidence: 99%